Graphene Quantum Dots: Effects of Graphene Quantum Dots on the Self‐Renewal and Differentiation of Mesenchymal Stem Cells (Adv. Healthcare Mater. 6/2016). Issue 6 (March 2016) - Qiu, Jichuan; Li, Deshuai; Mou, Xiaoning; Li, Jianhua; Guo, Weibo; Wang, Shu; Yu, Xin; Ma, Baojin; Zhang, Shan; Tang, Wei; Sang, Yuanhua; Gil, Pilar Rivera; et al.
Abstract : Fluorescent graphene quantum dots (GQDs) with good biocompatibility have great potential applications in biomedical areas. P. R. Gil, H. Liu, and co‐workers' investigation of the interactions between GQDs and mesenchymal stem cells (MSCs) is presented on page 702. When exposed to MSCs, GQDs can be ingested by MSCs and within a certain concentration range GQDs have no significant influence on self‐renewal potential of MSCs, but even promote and enhance their osteogenic and adipogenic differentiation at the level of mRNA and protein expression.